2022
DOI: 10.1186/s12871-022-01691-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine administration on analgesic, respiration and inflammatory responses in patients undergoing percutaneous endoscopic lumbar discectomy: a prospective observational study

Abstract: Background Local anesthesia has been recommended for percutaneous endoscopic lumbar discectomy (PELD) in recent years; however, the efficacy, including oxidative stress, inflammatory reactions and ventilation effects, when intravenous dexmedetomidine (DEX) is administered during PELD has not been described. Methods Sixty adult patients undergoing PELD were randomly allocated to either an intravenous DEX sedation group (Group A) or a normal saline g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Dexmedetomidine was reported by Zhang et al (2022) for its low respiratory depression. In our study, this phenomenon was also observed.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine was reported by Zhang et al (2022) for its low respiratory depression. In our study, this phenomenon was also observed.…”
Section: Discussionmentioning
confidence: 99%
“…Ye et al [ 20 ] reported that 66.6% of patients undergoing IELD under LA experienced pain intraoperatively, which was described as unbearable in 20%. Zhang et al [ 36 ] reported that some patients under LA could not tolerate the pain during endoscopic discectomy and required opioid administration during the operation. Airway management of a prone patient who has received opioids can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotension/bradycardia and delayed emergence are major shortcomings of dexmedetomidine, which can be prevented by ketamine intraoperatively. Studies have shown that adding DEX is a feasible method to address the analgesic defects associated with local anesthesia (12)(13)(14)(15).…”
Section: Local Anesthesiamentioning
confidence: 99%